Design and development of the Pediatric Urology Recovery After Surgery Endeavor (PURSUE) multicentre pilot and exploratory study - Kyle O Rove; Andrew C Strine; Duncan T Wilcox; Gino J Vricella; Timothy P Welch; Brian VanderBrink; David I Chu; Rajeev Chaudhry; Rebecca S Zee; Megan A Brockel; Douglas E. Coplen; Paul F. Austin; et al. (BMJ Open)
Introduction Lower urinary tract reconstruction in paediatric urology represents a physiologically stressful event that is associated with high complication rates, including readmissions and emergency room visits. Enhanced recovery after surgery (ERAS) protocol is a set of multidisciplinary, perioperative strategies designed to expedite surgical recovery without adversely impacting readmission or reoperation rates. Early paediatric urology data demonstrated ERAS reduced complications in this population.Methods and analysis In 2016, a working group of paediatric urologists and anaesthesiologists convened to develop an ERAS protocol suitable for patients undergoing lower urinary tract reconstruction and define study process measures, patient-reported outcomes and clinically relevant outcomes in paediatric and adolescent/young adult patients. A multicentre, prospective, propensity-matched, case–control study design was chosen. Each centre will enrol five pilot patients to verify implementation. Subsequent enrolled patients will be propensity matched to historical controls. Eligible patients must be aged 4–25 years and undergoing planned operations (bladder augmentation, continent ileovesicostomy or appendicovesicostomy, or urinary diversion). 64 ERAS patients and 128 controls will be needed to detect a decrease in mean length of stay by 2 days. Pilot phase outcomes include attainment of ≥70% mean protocol adherence per patient and reasons for protocol deviations. Exploratory phase primary outcome is ERAS protocol adherence, with secondary outcomes including length of stay, readmissions, reoperations, emergency room visits, 90-day complications, pain scores, opioid usage and differences in Quality of Recovery 9 scores.Ethics and dissemination This study has been registered with authors’ respective institution review boards and will be published in peer-reviewed journals. It will provide robust insight into the feasibility of ERAS in paediatric urology, determine patient outcomes and allow for iteration of ERAS implementations as new best practices and evidence for paediatric surgical care arise. We anticipate this study will take 4 years to fully accrue with completed follow-up.Trial registration number NCT03245242; Pre-results.